Effect of pore sizes and pore geometries on oil entrapment in water flooding process [electronic resource] - 369074 Mohd. Zafuan Che Zulkifli (2006)
Project Paper (Sarjana Muda Kejuruteraan (Petroleum)) - Universiti Teknologi Malaysia, 2006